Prototype of a System to Assist the Urologist in the Recognition of Urinary Bladder Tumors in MRI Images - Juarez Martinez, Ares Ulises; Puebla Lomas, Jaime Hugo; Serrano Talamantes, Jose Felix (Proceedings ... International Conference on Soft Computing & Machine Intelligence ISCMI ... (Online), 2023)
The proposal aims to develop a prototype system to detect possible bladder tumors. The system Will use image processing techniques, computer vision, segmentation, pattern recognition and machine learning. The prototype Will load images of the urinary bladder (hollow, distensible muscular organ) and obtain a classification of possible bladder tumors.